The unique Basque peace process: linking Basque and European generations for global transitional justice - Bengoetxea, Joxerramon (Oñati Socio-Legal Series, 2020)
This paper considers the recent and unique case of transitional justice in the Basque Country. Its uniqueness, from a comparative perspective, lies in its unilateral character. It is mostly through the pressure of Basque Society, together with the tough stance of the criminal justice system of Spain that ETA has dissolved. The analysis of this process thus discusses some issues of transitional justice, in tension with formal or traditional justice, and the relevance of this new field in Europe, Spain and the Basque Country. The paper spells out the most significant initiatives in the field of transitional justice adopted in the Basque case, stressing the importance of civil society, and the range of issues arising in a post-conflict situation where different agents have significantly different agendas. The paper concludes by suggesting steps towards an inclusive agenda on memory and narratives of the conflict capable of delivering truth and reconciliation.